Fabrication of SiO2/graphite composites with enhanced performance in supercapacitor electrodes - Jinjoo Jung; Chang-Duk Kim; Jihun Oh; Hanung Pae; Kyeong Tae Kang; Seung Beom Kang; Younjung Jo (APL Materials)
We present an efficient approach for synthesizing thin graphite-coated SiO2 composites (TGCSCs) for supercapacitor applications, by encapsulating SiO2 particles within multilayered graphene using thermal chemical vapor deposition. The TGCSC maintains the original morphology of the SiO2 particles, with the graphite layer exhibiting an interlayer distance of ∼0.34 nm. Surface analysis revealed the formation of Si–C and SiO–C bonds, which enhanced the conductivity and overall performance; in addition, acid treatment improved the electrode wettability by increasing the content of –OH groups, contributing to significant enhancement of the electrochemical performance. In a three-electrode system, the TGCSC electrode retained 99% of its initial capacitance after 5000 cycles in 1M H2SO4. These findings highlight the potential of SiO2/graphite composites as high-performance supercapacitor materials employing cost-effective and widely available resources.